THE INFLUENCE OF MOTIVATIONAL BEHAVIOR LEARNING AND EXERCISE OF THE ORGANIZATIONAL COMMITMENT - Syah Aji, Rizqon Halal; Saputra, Muhamad Malyan; Mariappan, Samila Devi A/P (Jurnal Ecoment Global, 2021)
Motivation to Learning has an important function in organizing commitment organized. Likewise with Displacement Knowledge Exercise also owns role in motivation description learn in influencing worker towards organizational commitment. So that employee continues to maintain their commitment to the organization. Therefore, this nature is very important in producing organization that is high quality and make a transfer towards training knowledge. This study was conducted on labor in the private sector with a total number of respondents of 189 workers. The research used was to identify and analyze the empirical model study with Partial Least square and moderating.